Autoantibody Positivity in Children with Chronic Diarrhea - Hale Tuhan; Aslı Aslan; Çiğdem Ecevit; Elif Azarsız; Neslihan Karaca; Funda Çetin; Necil Kütükçüler; Güzide Aksu (Galenos Yayinevi, 2020)
Aim:We aimed to determine the frequency of autoantibody antinuclear (ANA), peripheral anti-neutrophil cytoplasmic antibody (p-ANCA), anti-Saccharomyces cerevisiae antibody (ASCA), anti-pancreatic exocrine gland antibody (PAb), goblet cell antibody (GAb) positivities in children with the complaint of chronic diarrhea and inflammatory bowel disease (IBD). We also purposed to explore the role of these autoantibodies in the differential diagnosis of IBD.Materials and Methods:In our study, serum samples of 51 patients with the complaint of chronic diarrhea and 35 healthy controls were analyzed. Clinical and laboratory data at the time of serum sampling were collected and a differential diagnosis was made as the results of performed tests were recorded. For all patients, ANA, p-ANCA, ASCA, GAb, PAb positivities were evaluated by indirect immunofluorescence. The chronic diarrhea group was divided into two groups, namely, the IBD group and non-IBD group.Results:In the chronic diarrhea group, 11 (21.6%) patients had ANA, 3 (5.9%) had p-ANCA, 1 (2%) had PAb, 1 (2%) had Gab and 1 (2%) had ASCA positivity. From the 35 cases of the control group, 8 (22.9%) had ANA, 7 (20%) had ASCA positivity. In the control group, ASCA was found to be high (p=0.007). Six cases were diagnosed as IBD; 1 (16.7%) had ANA, 1 (16.7%) had p-ANCA, 1 (2%) had Gab and 1 (2%) had ASCA positivity. ASCA and GAb positivities were significantly more frequent in the IBD group (p=0.006, p=0.006, respectively).Conclusion:ASCA was determined to be significantly higher in the control group. High positivity in the control group showed that the percentage of nonspecific positivity may be high for this test. ASCA and GAb of those patients with a diagnosis of IBD were found significantly higher. The serologic tests which depend on p-ANCA, ASCA, PAb, GAb can be supportive of diagnoses and differential diagnoses of IBD. Autoantibodies in IBD may be used as a supportive diagnostic tool in selected cases, rather than as the diagnosis of IBD as routine practice.